Reformulasi Seni Pertunjukan Sidandang: Model Aktualisasi Konservasi Seni dan Budaya Berbasis Local Wisdom Kelurahan Purwosari Kecamatan Mijen - Isna Vardianawati; Ruly Indra Darmawan; Budi Saryanto; Zahro Faradisa (Faculty of Cultural Studies, Universitas Brawijaya, 2023)
Purwosari Village is a village with cultural potential. The traditional dance called Jaran Eblek and the existence of the Sidandang Monument with its various philosophical meanings are local cultural heritages that have the potential to be more widely known by the public. The objective of this community service initiative is to reinterpret the local traditional dance form, create a new dance for female practitioners, and organize a cultural festival around the Sidandang Monument to expand the reach of the general public, enabling them to learn about and engage with it. The methods employed include cultural awareness campaigns and training sessions on creating new dances for young female practitioners. The results achieved in the implementation of the community service program “Reformulation of Sidandang Performing Arts: A Model for the Actualization of Art and Cultural Conservation Based on Local Wisdom in Purwosari Village, Mijen District” are: (1) The local community, especially artists, are more aware of the importance of preserving and conserving existing cultural wealth; (2) Purwosari Village has gained an additional traditional dance, namely the Tugu Sidandang Dance; (3) Tugu Sidandang is now more widely known by the outside community; (4) Local SMEs have been further assisted by the regular cultural festivals held there. The benefits of this community service activity are: (1) Lecturers can contribute their knowledge and ideas to the community; (2) The culture of Purwosari Village becomes more vibrant.